PENGARUH PENGGUNAAN MODEL STAD TERHADAP AKTIVITAS BELAJAR PADA PELAJARAN SOSOLOGI KELAS X MAS AL-MUSTAQIM - Andayani, Tri; Zakso, Amrazi; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of the use of the STAD model on student learning activities in sociology subjects in class X IPS MAS AL-MUSTAQIM. The research method used is using ex post facto. The results showed that: 1) The STAD model was used in class X in sociology learning is an average value of 40.22 classified in the high category. 2) Student learning activities in learning sociology obtained an average value of 36.83 classified in the low category. 3) The effect of the use of the STAD model on learning activities in sociology subjects hypothesized test results of significance values of (0.004 < 0.05) and t arithmetic values (2.973) > t table values (2.001), then Ho is rejected and Ha is accepted. So there is a positive and significant effect between the use of the STAD model and student learning activities in sociology subjects. 4) The magnitude of the effect of using the STAD model on sociology learning activities of 0.117 is equal to 11.7%. This means that the percentage of the effect of using the STAD model on sociology learning activities is 11.7% while the remaining 88.3% is influenced by other variables not examined in this study.Â Keywords:Learning Activity, Sociologi Subjects, and Use Of The STAD Model